Optimizing expanded carrier screening for China: Multi-center study establishes 202-gene panel with optimal cost-effectiveness in preconception and prenatal care - Yulu Yang; Yuting Hang; WeiSheng Cheng; Yunxia Cao; Zhaolian Wei; Jing Yuan (PLoS ONE, 2026)
Objective To evaluate the cost-effectiveness of different expanded carrier screening (ECS) panels for couples in China during preconception and early pregnancy (≤12 +6 weeks) based on a multi-center cohort study. Methods A multicenter, population-based study was conducted across 22 prenatal diagnosis centers in China from August 2022 to June 2023, enrolling 2,996 participants. Geographical distribution and at-risk gene frequencies were analyzed, categorizing the 222-gene panel into three groups: Panel A (222 genes), Panel B (188 genes, compliant with international guidelines), and Panel C (202 genes, optimized for the Chinese population). Decision-tree models assessed cost-effectiveness in two clinical scenarios: Preconception and During Pregnancy. Additionally, two distinct outcomes were employed: payoff 1 was defined as the number of necessary medically termination, while payoff 2 was the number of newborns free of recessive monogenic disorders. Results As anticipated, European screening recommendations demonstrated limited applicability to the Chinese population. Panel A incurred the highest total cost in both the Preconception (US $5,214) and During Pregnancy (US $990) models. In the Preconception model, the incremental cost-effectiveness ratio for Panel C was US $74,869 per necessary termination and US $23,999 per additional healthy newborn without genetic disorders, compared to Panel B. In the During Pregnancy model, Panel B was the most cost-effective, yielding savings of US $580 per necessary termination and US $2,052 per healthy newborn compared to Panel C. Conclusion For Chinese couples, the 202-gene panel (Panel C) is the most cost-effective option in both preconception and prenatal settings. However, for couples prioritizing comprehensive screening over cost, the 222-gene panel (Panel A) provides greater clinical value at a higher cost.